EDUKASI DONOR DARAH BERBAGI KEHIDUPAN MENINGKATKAN KESADARAN PENDONOR SEJAHTERA DAN STOK DARAH - Iswati, Iswati; Qomariah, Siti Nur; Jannah, Fitriatul; Susanti, Susanti; Mohammad, Alfian Irfhani (Community Development in Health Journal, 2025)
Introduction & Aim: The need for blood is high in healthcare settings due to its frequent use in medical procedures. However, blood supplies have been limited, particularly since the COVID-19 pandemic in 2020. The goal of this community service activity is to increase blood supplies, raise public awareness prosperous donor, and foster humanitarian cooperation. Method of Activity: This community service activity was in the form of blood donation and education about donor welfare. The technical strategies used include: 1) socializing blood donation activities to target participants through posters and social media, 2) coordinating the implementation of examinations and blood collection flows, 3) coordinating lecture hours that will be used for blood donation times so that all students can participate in the activity, 4) carrying out blood collection by the Blood Transfusion Installation at several predetermined hours, 5) distributing food to donor participants who do not pass the initial examination and providing attractive souvenirs for blood donor participants who pass the selection. Results: Ninety-six people successfully donated their blood, increasing the blood supply in the Blood Transfusion Installation, Dr. Soetomo Regional Hospital, Surabaya. However, 29 people were unable to donate because they did not meet the requirements. Discussion: This community service is a form of integration of research results on the function of blood donors and increasing cross-sectoral collaboration to improve public health.